Thanksgiving is for giving thanks - Sutherland, Margaret; Lamut, Sonja (New York : Grosset & Dunlap, 2000)
A child lists all the things for which he is thankful, especially at Thanksgiving.
Keywords: Gratitude -- Fiction; Thanksgiving Day -- Fiction